Perempuan dan Islam di Media Baru: Dalam Kasus Cadar Baru dalam Instagram - Perdana Aysha Puteri (Religia, 2022)
Currently, some niqab wearers are active in expressing themselves on social media. Moreover, the niqab has its fashion trend. The internet and social media allow niqab wearers to actively and freely engage in social interactions, especially on current social media platforms. they are different from other niqab wearers who are often shown wearing conventional niqab (dark colors, such as black, dark blue, dark brown, etc.) and take advantage of online activities as an alternative means of their strict restrictions in communication and relationships based on their religious ideology. These new niqab wearers tend to be colorful, fashionable, and active, as seen in their offline and online activities. However, the emergence of this new trend raises pros and cons. This paper will examine two things, first is regarding discourses that shape the moral and Islamic construction of women’s bodies in Indonesian contexts. The second is how the emergence of a new niqab trend related to the discourse on the women's body.